The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/agronomy11081552
|View full text |Cite
|
Sign up to set email alerts
|

Management of Phosphorus in Salinity-Stressed Agriculture for Sustainable Crop Production by Salt-Tolerant Phosphate-Solubilizing Bacteria—A Review

Abstract: Among the environmental factors, soil salinity is one of the most detrimental factors affecting plant growth and productivity. Nutritional-imbalance is also known as one of the negative effects of salinity on plant growth and productivity. Among the essential plant nutrients, phosphorus (P) is a nutrient in which the uptake, transport, and distribution in plant is adversely affected by salinity-stress. Salinity-stress-mediated low a P availability limits the crop production. Adding additional P fertilizer is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 191 publications
2
48
0
1
Order By: Relevance
“…Accessibility to vital nutrients is usually reduced by salt stress [ 79 , 85 , 86 ] in most plants. This study revealed that a minimum concentration of Na + was observed in control, and a maximum concentration was found at a high salinity level (150 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Accessibility to vital nutrients is usually reduced by salt stress [ 79 , 85 , 86 ] in most plants. This study revealed that a minimum concentration of Na + was observed in control, and a maximum concentration was found at a high salinity level (150 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall also increases total phosphorus concentration in urban areas via storm drains [26]. The highest contamination level of the Utrata River by phosphorus during the months of June-September coincides with the intensification of agricultural activity in these areas [27].…”
Section: Discussionmentioning
confidence: 98%
“…These PGPBs enhance plant growth and reduce salt absorption, which increases yield [14]. Under salt stress, the uptake and accumulation of plant nutrients such as N [15], P [16], and K reduces in plants. However, salt-tolerant plant growth-promoting rhizobacteria improve nutrient uptake and translocation in plants by employing biochemical and physiological mechanisms [17].…”
Section: Introductionmentioning
confidence: 99%